MANAJEMEN ASET DALAM PENGELOLAAN ASET (TANAH DAN BANGUNAN) PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KOTA BATU TAHUN 2014 - , SALMAN FARIZY ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study is analyze the implementation of the asset management of the land and buildings on BPKAD of Batu city by using of importance performance analysis (IPA) and how the strategy should be applied in optimizing the implementation of asset management of land and buildings by using SWOT analysis. This study used a purposive sampling technique with a number of the respondents 42. The importance of the analysis results item statement tops the list i.e registration (certification) of land assets. Item statement was ranked the last planning needs in formulating the goods belonging to the see the relationship with the procurement of goods has been running as the basis for action in fulfillment of the needs of the future.The use of all assets land and buildings are optimal. For the level of performance who ranked first was logging, logging and distortion of information documents relating to land and building assets.For the last stage is the use of all assets land and buildings are optimal. Development and implementation of strategies in the management of assets (land and buildings), among other areas. Improving the quality of human resourcestop understanding of asset management, The Asset Management System Optimization of Batu city (SIMAKOBA), which integrates and collaborates with other parties related to the optimization of assets (land and buildings) area. Keyword: Asset Management, Importance Perforance Analysis (IPA) dan analysis SWOT